Fertilización foliar a base de algas marinas en el cultivo de pepino (Cucumis sativus L.) en época lluviosa en la zona de Quevedo. - Pico Martínez, Karen Tatiana (2017)
The present research was carried out with the purpose of evaluating the agronomic behavior and production of the cucumber crop (Cucumis sativus L). In response to foliar fertilization based on seaweed. The test was carried out on land at the Maria Gabriela estate, located at Km 10.2 of the Quevedo - Mocache road, between coordinates 1 ° 05'28.4 "S 79 ° 29'38.5" W, at an altitude of 67 m.s.n.m. A complete 2x3 + 2 random blocks design was used in 3 replicates. Two foliar fertilizers were studied: Alga 600 and Microalgae K +, in three doses: 0.5, 1.0 and 1.5 kg / ha, whose interactions were compared with two controls: absolute and Nitrofoska. With Alga 600 plants were obtained with guides of longer length at 45 days (131.7 cm), shorter flowering time (27.7 days) and greater number of fruits per plant (4.0 fruits), with larger diameter (4.5 cm), length (22.7 cm) and weight (339.8 g), which triggered a higher yield per hectare (29416.8 kg). The dose of 1.5 kg / ha reflected longer guides at 45 days that exceeded in 2.4 and 4.3 cm, a decrease of 1.3 and 0.5 days in flowering time, compared to the doses of 1.0 and 0.5 kg / ha. The fruit yield per plant was higher with the 1.5 kg / ha dose with 4.7 fruits, which presented better characteristics of length, diameter and weight with values of 23.8 cm, 4.7 cm, 377.3 g, respectively. The yield reached with the dose of 1.5 kg / ha exceeded in 4727.7 and 7879.5 kg / ha at the doses of 1.0 and 0.5 kg / ha, that is to say an increase of 16.82 and 31.58% in the harvest. The treatment of 1.5 kg / ha of Alga recorded guides 2.8 cm below the Nitrofoska Witness, 27.3 days at flowering, producing an equal number of fruits per plant than the mentioned control with 4.8 cucumbers. The application of 1.5 kg / ha of Alga 600 produced fruits of 0.1 cm diameter below the Nitrofoska application, being equal in length with 24.0 cm each, with a fruit weight of 6.8 g below the 395.3 g of Weight of Nitrofoska. The yield per hectare was higher with Nitrofoska with 34144.5 kg, which surpassed in 525.3 kg / ha to the application of 1.5 kg / ha of Alga 600. With the application of Nitrofoska it was obtained a 40% of profitability, whereas when applying 1.5 kg / Ha of Alga 600 yielded 38% profitability, proving to be a very good treatment to be applied in agricultural production systems. Keywords: cucumber crop, foliar fertilizer, seaweed in agriculture.